The cutaneous effects of androgens and androgen-mediated sebum production and their pathophysiologic and therapeutic importance in acne vulgaris - James Q. Del Rosso; Leon Kircik (Taylor & Francis Group, 2024)
AbstractBackground: The recognition of an association between the development of acne vulgaris (AV) and pubertal hormonal changes during adolescence dates back almost 100 years. Since these formative observations, a significant role of circulating hormones in the pathophysiology of AV and other cutaneous disorders has been established.Aims: This review article aims to provide an overview of clinical and preclinical evidence supporting the influences of androgens on the skin and their therapeutic importance in AV pathophysiology.Results: The cutaneous effects of hormones are attributable, to a large extent, to the influence of steroid hormones, particularly androgens, on sebocyte development and sebum production in both sexes. Androgen-mediated excess sebum production is implicated as a necessary early step in AV pathophysiology and is therefore considered an important therapeutic target in AV treatment. Although the local production and/or activity of androgens within the skin is believed to be important in AV pathophysiology, it has received limited therapeutic attention.Conclusions: We have summarized the current evidence in support of the therapeutic benefits of targeted hormonal treatment to decrease androgen-stimulated sebum production for the effective and safe treatment of AV in both male and female patients.